Chemical Characteristics of Water Hyacinth Pellet Fertilizer with Different Adhesive Materials - Nukhak Nufita Sari; Ronny Mulyawan; Irvan Indra Resnawan (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2026)
High application of inorganic fertilizers can negatively affect soil fertility and environmental sustainability. Organic farming uses organic materials to improve soil quality and support sustainable crop production. Water hyacinth (Eichhornia crassipes), an invasive aquatic weed, has potential as a raw material for pellet organic fertilizer. This study aimed to evaluate the chemical characteristics of water hyacinth pellet fertilizer using different adhesive materials in accordance with SNI 7763:2024 and to determine the most suitable adhesive material. The research was conducted using a descriptive-experimental method with three adhesive treatments: ET1 = water hyacinth flour + tapioca flour; ET2 = water hyacinth flour + wheat flour; and ET3 = water hyacinth flour + rice bran flour. Each treatment was repeated three times. All treatments used a ratio of 1:2:4 (water: water hygienist: adhesive). Chemical analyses included pH, organic C, total N, total P, total K, total macronutrients, and the C/N ratio. The results showed that pellet fertilizers with tapioca and wheat flour adhesives met the SNI standards for pH and organic C but did not meet the standards for total macronutrients and the C/N ratio. Pellet fertilizer with rice bran flour adhesive met the SNI standards for pH, organic C, and total macronutrients, although its C/N ratio exceeded the maximum standard limit. Rice bran adhesive also produced the highest total N, P, K, and total macronutrient contents among the treatments. Overall, rice bran flour was identified as the most suitable adhesive for improving the chemical quality of water hyacinth pellet fertilizer, in accordance with SNI 7763:2024.